Rethinking tenderness in the early poetry of Juan Gelman - Bollig, B (Routledge, 2023)
The poetry of Juan Gelman (1930–2014) is eminently suited to an edition of BSS that simultaneously celebrates a centenary of Hispanist research in the UK and attempts to survey the current state of the field. Gelman—poet, journalist and political activist—with an oeuvre that emerges from the socially engaged verse of the 1950s, engaging with Anglophone poetry, pseudonymous translations mysticism, and culminating in the Premio Cervantes 2007. An assessment of his early work, particularly the presence of ternura therein, draws on influential work in affect theory and speaks to signal moments in the history of UK Hispanism.